Suasana Komunikasi Pemasaran menjelang Pilkada DKI Jakarta 2017 - Ilham Albar Pane (Jurnal Komunikasi, 2016)
This paper tried to discuss the process of political communication in the pilkada DKI 2017. The discuss based on the approach of political communication that used the method of marketing communication. Results of the analysis showed that the integrated marketing communication (IMC) method became the main choise in the marketing of runnours of politics in the Pilkada DKI 2017. According to IMC method, then the media of politics of marketing communication became the important instrument in Pilkada DKI 2017.Kata-kata kunci : Komunikasi, pemasaran, politik.